2018
DOI: 10.1097/mao.0000000000002045
|View full text |Cite
|
Sign up to set email alerts
|

The Insertion Results of a Mid-scala Electrode Assessed by MRI and CBCT Image Fusion

Abstract: Objectives: To investigate the results of clinical surgical insertions with a Mid-scala array (HIFocus Mid-Scala Electrode, HFms). Study Design: Consecutive retrospective case study. Settings: Tertiary referral center. Patients: Analyses of imaging data of 26 consecutive patients (31 insertions) implanted with the HFms. Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…of electrode per type/brandNo. of cases reported tip fold-overABCTimm et al (2018)275 (CT)275 (F28, F24, F20, F16)0Sipari et al. (2018)23 (CT)MS (23)2Gabrielpillai et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…of electrode per type/brandNo. of cases reported tip fold-overABCTimm et al (2018)275 (CT)275 (F28, F24, F20, F16)0Sipari et al. (2018)23 (CT)MS (23)2Gabrielpillai et al.…”
Section: Resultsmentioning
confidence: 99%
“…Electrode scalar deviation is another important and the most traumatic event that could happen inside the cochlea during electrode placement. A total of 26 peer-reviewed publications were found reporting on intra-cochlear electrode array scalar deviation in patient cases with the current commercially available electrode types (McJunkin et al., 2018; Mittmann et al., 2017; Koka et al., 2018; Dirr et al., 2013; Sipari et al., 2018; Jia et al., 2018; Aschendorff et al., 2017; Fischer et al., 2015; Shaul et al., 2018; Ketterer et al., 2017; An et al., 2017; O'Connell et al., 2017a; O'Connell et al., 2017b; Lathuillière et al., 2017; O'Connell et al., 2016a; O'Connell et al., 2016b; Wanna et al., 2015; Nordfalk et al., 2016; Mittmann et al., 2015a; Mittmann et al., 2015b; Mittmann et al., 2015c; Boyer et al., 2015; Wanna et al., 2014; Nordfalk et al., 2014; Aschendorff et al., 2011; Wanna et al., 2011; Lane et al., 2007) and were summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…McJunkin et al [36] described scala translocation in 3 out of 23 insertions (13%), whereas Aschendorff et al [32] reported of no scala translocations. In summary, the translocation rates of the SME appear to be considerably lower than those reported for stylet-type PMEs, in the publications, their translocation rates have varied from 15.8% up to 52.3% [1,2,16,22,40,41].…”
Section: Discussionmentioning
confidence: 78%